1990
DOI: 10.1002/cjce.5450680501
|View full text |Cite
|
Sign up to set email alerts
|

Sparged loop reactors

Abstract: Circulating bubble columns or loop reactors form one of the important classes of modified bubble columns. The present paper analyses the performance of external loop air lift reactors (EL‐ALR). The EL‐ALR has many advantageous features especially at large scale. These arise from its feature of having controlled liquid circulation which is the key parameter for the design and operation of EL‐ALR contactors. Therefore, a reliable and generalised circulation model has been presented. The reliability of the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 154 publications
(77 citation statements)
references
References 82 publications
2
73
0
2
Order By: Relevance
“…This is because the larger hydrodynamic resistance in the ELAMR caused lower W LD that induced more intensive bubble coalescence. Joshi et al (1990) and Bendjaballah et al (1999) also noted that the resistance in the ELAR, and thereby W LD , and the geometry of the downcomer influenced the regime transitions. On the other hand, Vial et al (2002) reported that the hydrodynamic resistance had a minor influence on the regime transitions.…”
Section: Hydrodynamic Regimesmentioning
confidence: 94%
“…This is because the larger hydrodynamic resistance in the ELAMR caused lower W LD that induced more intensive bubble coalescence. Joshi et al (1990) and Bendjaballah et al (1999) also noted that the resistance in the ELAR, and thereby W LD , and the geometry of the downcomer influenced the regime transitions. On the other hand, Vial et al (2002) reported that the hydrodynamic resistance had a minor influence on the regime transitions.…”
Section: Hydrodynamic Regimesmentioning
confidence: 94%
“…Some of the applications of these are discussed in the subsequent sections. The governing equations for single phase flows, the EulerianEulerian approach and volume of fluid approach may be found in many text books (for example, Ranade [106], Ranade and coworkers [18,19,54,[108][109][110], and manuals of commercial CFD vendors). These are, therefore, not repeated and discussed here.…”
Section: International Journal Of Chemical Engineeringmentioning
confidence: 99%
“…Weiland and Onken [12], Verlaan [13], Gavrilescu and Tudose [14], and Vial et al [15] have performed experimental studies and reported values of axial dispersion coefficients in the risers of external loop airlift reactors. Joshi et al [16] have done a detailed hydrodynamic modeling of different sections of external loop air lift reactors and have proposed a unified correlation for the axial dispersion coefficient D L . Recently, Roy et al [17] have performed extensive CFD analyses of the flow and axial dispersion phenomena in the riser of an external loop airlift reactor.…”
Section: Introductionmentioning
confidence: 99%